An Integrative Approach to Study Bacterial Enzymatic Degradation of Toxic Dyes - Mishra, Arti; Takkar, Simran; Joshi, Naveen Chandra; Shukla, Smriti; Shukla, Kartikeya; Singh, Anamika; Manikonda, Anusha; Varma, Ajit (Frontiers in Microbiology, 2022)
Synthetic dyes pose a large threat to the environment and consequently to human health. Various dyes are used in textile, cosmetics, and pharmaceuticals industries, released into the environment without any treatment, thus adversely affecting both the environment and neighbouring human populations. Several existing physical and chemical methods for dye degradation are effective but have many drawbacks. Biological methods over the years have gained importance in the decolourisation and degradation of dye and have also overcome the disadvantages of physiochemical methods. Furthermore, biological methods are eco-friendly and lead to complete decolourisation. The mechanism of decolourisation and degradation by several bacterial enzymes are discussed in detail. For the identification of ecologically sustainable strains and their application at the ﬁeld level, we have focused on bioaugmentation aspects. Furthermore, in silico studies such as molecular docking of bacterial enzymes with dyes can give a new insight into biological studies and provide an easy way to understand the interaction at the molecular level. This review mainly focuses on an integrative approach and its importance for the effective treatment and decolourisation of dyes.